2018
DOI: 10.1186/s13047-018-0250-9
|View full text |Cite
|
Sign up to set email alerts
|

National profile of foot orthotic provision in the United Kingdom, part 2: podiatrist, orthotist and physiotherapy practices

Abstract: BackgroundA national survey recently provided the first description of foot orthotic provision in the United Kingdom. This article aims to profile and compare the foot orthoses practice of podiatrists, orthotists and physiotherapists within the current provision.MethodQuantitative data were collected from podiatrists, orthotists and physiotherapists via an online questionnaire. The topics, questions and answers were developed through a series of pilot phases. The professions were targeted through electronic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…Variances in appointment times were evident between regions and between contracted and inhouse services, with all appointment times relatively short (average times between 18 and 41 min). This finding is confirmed by a recent study which examined foot orthotic provision in the United Kingdom25; reporting that the majority of orthotists (62%) had 15–30 min for clinical assessments and 15% reported having <15 min appointments. These appointment times were significantly lower than those reported for podiatrists and physiotherapists, who were 11.0 and 13.2 times more likely, respectively, to have 45–60 min appointments 25.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Variances in appointment times were evident between regions and between contracted and inhouse services, with all appointment times relatively short (average times between 18 and 41 min). This finding is confirmed by a recent study which examined foot orthotic provision in the United Kingdom25; reporting that the majority of orthotists (62%) had 15–30 min for clinical assessments and 15% reported having <15 min appointments. These appointment times were significantly lower than those reported for podiatrists and physiotherapists, who were 11.0 and 13.2 times more likely, respectively, to have 45–60 min appointments 25.…”
Section: Discussionsupporting
confidence: 63%
“…This finding is confirmed by a recent study which examined foot orthotic provision in the United Kingdom25; reporting that the majority of orthotists (62%) had 15–30 min for clinical assessments and 15% reported having <15 min appointments. These appointment times were significantly lower than those reported for podiatrists and physiotherapists, who were 11.0 and 13.2 times more likely, respectively, to have 45–60 min appointments 25. It also supports previous research which reported that when orthotists were asked if they provided AFO–footwear combination tuning 27% said they did not tune due to a lack of time 26.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Despite the historical and relatively common usage of clinical footwear interventions in children with mobility impairment, 5 6 there has been a lack of common understanding of how to define and characterise this intervention. The collective opinion of the expert panel and the consensus formed through the inductive and iterative process of this study allowed novel ideas to be synthesised alongside previously published information.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 76.6% of respondents reported that the amount of time they had per face-to-face appointment had increased compared with before the pandemic, which is in line with previous research which reported that orthotic appointment times were on average between 15 and 40 minutes which are below the recommended appointment times advised by BAPO. 4,12 Most orthotists surveyed reported that they continued to remain at work during the pandemic, with only 9% (n 5 7) reporting that they were furloughed, all of whom reported being employed by a contractor.…”
Section: Discussionmentioning
confidence: 99%